Crowd counting based on Difference Images - Chen, Jinyan (Elektronika ir Elektrotechnika, 2013)
Many crowd counting methods were proposed in recently years. Most of these methods were implemented by extracting the human silhouette from the background image. But under some conditions it is difficult get a clear background image. In this paper a crowd counting method based on the images difference is proposed, instead of extract silhouette from background, the surveillance was divided into frames. Difference image of two frames is calculated by images subtraction. Then image features were extracted based on difference image and the crowed count is calculated based on these features. Experiment result show that this method is feasible. DOI: http://dx.doi.org/10.5755/j01.eee.19.2.3475